The Artistic Access Residency Creazioni Accessibili: Audio Description Dramaturgy in Contemporary Dance - Comuniello, Giuseppe; D’Amico, Flavia Dalila; Guarino, Camilla (Performance Matters, 2025)
This article focuses on the challenges that the integration of audio description (hereafter AD) into contemporary choreography provides, by analyzing two artistic processes and their applied solutions. The examined examples described here took place in the residency Creazioni Accessibili (Accessible Creations) in Rome/Italy. This residency features Giuseppe Comuniello (blind performer and choreographer) and Camilla Guarino (dramaturg) as mentors, is curated by Flavia Dalila D’Amico, and is produced by the National Centre of Dance Production Orbita Spellbound in Rome. The aim is to discover both emotional and affective ways to make contemporary dance performances accessible for blind and visually impaired audiences by engaging with AD as a means to provide layers of meaningful and multisensory access to the dramaturgy and poetics of a specific show. Every year, the curator and mentors select an artistic project through an open call, offering the possibility for a choreographer to discover suitable access strategies for his/her dance work. During the work phases, the residency includes both mixed vision mentorship and feedback sessions with blind and visually impaired spectators, using co-design as a method to test the AD and reflect the concrete desires of access-deserving people. Co-design means collaborating with people with specific lived experience to create something new, like a service, product, or research project. It’s not just about getting feedback; it’s about sharing decision-making power and working together to shape the final product, which in this case is the access dramaturgy of a contemporary dance work. So every year an artist can co-design access strategies with blind mentors and test the results with blind community members. This article combines Flavia Dalila D’Amico’s lens as scholar and residency curator with Giuseppe Comuniello and Camilla Guarino’s notes as mentors and dance artists. These three authors describe and discuss how different the solutions were tried out in the first two years of the residency.Plain Language Abstract (adapted by Kelsie Acton with Daniel Foulds)This essay talks about making audio description part of dance. Audio description is when someone tells Blind or visually impaired people what the dance looks like. Creazioni Accessibili (Accessible Creations) is an arts program in Rome. This essay looks at how two dances were made at Creazioni Accessibili. Flavia Dalila D’Amico organized Creazioni Accessibili. Guiseppe Comuniello is a blind performer and choreographer. Camilla Guarino is a dramaturg. A dramaturg helps the artists make art that has meaning and makes people feel. People might see, hear, smell, or feel performance. So dramaturgy is about making meaning and feeling through the senses. They all worked on these dances. The goal was to make Blind and visually impaired people feel the dance, emotionally and through descriptions of what dancers see when moving and what other people see when watching them move. The artists tried out different ways of doing audio description for dance. During the process, Blind people told the artists if the audio description worked. This means that Blind people shared their knowledge with artists so they can make something new together. In this essay, Flavia Dalila D’Amico, Guiseppe Comuniello, and Camilla Guarino write together about the different types of audio description they have tested. Some of the types of audio description they tested weredescribing only the dancers’ movement, describing what the people watching did as well as the dancers, describing what the movement made them think of, and having two people describe the same movement.